The Role of Generative Artificial Intelligence in Personalized Learning: Opportunities, Challenges, and Ethical Implications - Ahmad Nur Kholis (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study aims to analyze the role of Generative Artificial Intelligence (GenAI) in realizing personalized learning, highlighting the opportunities, challenges, and ethical implications associated with it. The research approach uses a qualitative method through a literature review that examines various scientific sources such as reputable journals, UNESCO reports, and educational policies related to AI. The study results indicate that GenAI has the potential to revolutionize the education system by creating adaptive, interactive, and individual-centered learning experiences. However, the integration of this technology faces structural obstacles in the form of a digital divide, low technological literacy, and weak ethical governance in its implementation. Legal and ethical aspects are crucial dimensions to ensure algorithmic transparency, data protection, and fair access for all students. Therefore, an educational policy oriented towards the principles of responsible AI is needed, accompanied by increased digital and ethical literacy for educators and students. This study emphasizes that the use of AI in education must be directed as an instrument of human empowerment, not a replacement for the role of educators, thus creating an inclusive, reflective, and equitable learning system in the digital era.